Credit access, tax structure and the performance of Malaysian manufacturing SMEs - Cheong, Calvin W. H. *; Lee, M. H.; Weissmann, M. A. (Emerald, 2020)
Purpose: This study investigates the effects of credit access and tax structures on the performance of Manufacturing SMEs in Malaysia. Design/methodology/approach: This study uses the dynamic panel system generalized method of moments, controlling for firm-specific as well as macroeconomic effects Findings: The paper finds that (1) debt funding is not conducive to SME performance; (2) access to non-bank credit sources and tax incentives support SME performance by lowering opportunity costs of riskier projects; (3) existing tax structures in Malaysia inhibit SME growth and encourage manipulation of accounts; and (4) investors in Malaysia prefer SMEs that are more conservative in their accounting and taxation practices. Research limitations/implications: Access to Malaysian SME data is restricted. Although robust methods are used, there is a chance that different conclusions may arise with a much larger sample. Practical implications: The findings provide clear direction in the discussion and enactment of new policies that support SME growth especially in support of non-bank credit sources instead of revising tax policies. The paper also contributes by providing guidance to future SME studies that are inhibited by limited access to data. Originality/value: SME-related studies on credit access and tax structures have often relied on traditional metrics (e.g. total amount of bank loans; tax expenses) to measure its impact on entrepreneurial/SME performance. Although relevant to the past, financial policies have evolved to embrace Industrial Revolution 4.0. This paper is a shift from the traditional by investigating the impact of new and innovative sources of funding such as incubators and crowdfunding. Also, since one cannot exist without the other, examining the joint impact of credit access and tax structures provides a more holistic view on policy-making, something prior studies have not addressed.